2021
DOI: 10.1016/j.aohep.2020.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of liver biochemical parameters for COVID-19 mortality

Abstract: Introduction Coronavirus Disease 2019 (COVID-19) has brought great challenges to global public health. However, a comprehensive analysis of the relationship between liver biochemical parameters and COVID-19 mortality is quite limited. Methods We searched the following electronic databases: PubMed, Embase, Cochrane Library, Web of Science, Scopus, Wanfang and China National Knowledge Infrastructure database until May 5, 2020. STATA software was used for the statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…Also, older age, male sex, comorbidity, and obesity can impact survival in patients with COVID-19. 3,4,[24][25][26][27][28] We found significant differences between the survivors and the non-survivors in terms of age, gender, lymphocyte, NT-proBNP, LDH, ferritin, CRP, and procalcitonin, as showed by recently published studies.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Also, older age, male sex, comorbidity, and obesity can impact survival in patients with COVID-19. 3,4,[24][25][26][27][28] We found significant differences between the survivors and the non-survivors in terms of age, gender, lymphocyte, NT-proBNP, LDH, ferritin, CRP, and procalcitonin, as showed by recently published studies.…”
Section: Discussionsupporting
confidence: 76%
“…1,2 Due to the COVID-19 is associated with a high risk of mortality and morbidity in critically ill patients, lots of clinical studies have focused on the identification of prognostic factors to reduce COVID-19 associated mortality. 3,4 The level of serum lactate is the most commonly used biomarker for the management of critically ill patients in the emergency department and intensive care unit (ICU). 5 Hyperlactatemia or elevated levels of serum lactate may be caused by different clinical settings including sepsis, liver diseases, shock, and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, a minority of them may progress into liver failure[ 7 ]. Some studies suggested that abnormal liver biochemical tests, especially elevated aspartate aminotransferase (AST), be closely associated with severe outcome[ 2 , 8 ] and death[ 9 , 10 ] in COVID-19 patients. Contrarily, others indicated no significant correlation of abnormal liver biochemical tests with mortality[ 11 ] or disease severity[ 12 ].…”
mentioning
confidence: 99%
“…The increased transaminase activity in patients with COVID-19 is thought to be a predictor of a poor outcome of the disease [29][30][31][32][33]. The causes of liver dysfunction in COVID-19 may vary: it can be either direct damage to hepatocytes by the SARS-CoV-2 virus or a cytokine storm result.…”
Section: Resultsmentioning
confidence: 99%